Efficacy and safety of PXL770, a direct AMP kinase activator, for the treatment of non-alcoholic fatty liver disease (STAMP-NAFLD): a randomised, double-blind, placebo-controlled, phase 2a study. (November 2021) - Cusi, Kenneth; Alkhouri, Naim; Harrison, Stephen A; Fouqueray, Pascale; Moller, David E; Hallakou-Bozec, Sophie; Bolze, Sebastien; Grouin, Jean-Marie; Jeannin Megnien, Sophie; Dubourg, Julie; Ratziu, Vlad
Summary: Background: AMP kinase (AMPK) is an energy sensor implicated in regulation of lipid metabolism, inflammation, and insulin sensitivity. We aimed to assess efficacy and safety of PXL770, a novel direct AMPK activator, in patients with non-alcoholic fatty liver disease (NAFLD). Methods: STAMP-NAFLD, a randomised, double-blind, placebo-controlled phase 2a study, was done across 15 US clinical sites. Patients aged 18–75 years with liver fat content of at least 10% at baseline when assessed by MRI-proton density fat fraction (MRI-PDFF) were eligible. Patients were randomly assigned (1:1:1:1), via an interactive web response system, to receive oral PXL770 250 mg once daily, 250 mg twice daily, or 500 mg once daily, or matched placebo. Patients were stratified according to type 2 diabetes status and study site. The primary endpoint was relative change in liver fat content from baseline compared with placebo at week 12, assessed by MRI-PDFF. The primary endpoint was analysed in an ANCOVA model with treatment and stratification criteria as factors and baseline liver fat content as a covariate in the modified intention-to-treat population, defined as all as-randomised patients who received at least one dose of study treatment. Safety was analysed in the safety population, defined as all as-treated patients receiving at least one dose of the study treatment. The trial has been completed and the final results are reported. The trial is registered with ClinicalTrials.gov, NCT03763877 . Findings: Between March 29, 2019, and March 13, 2020, 387 patients were screened, of whom 120 were included in the modified intention-to-treat and safety analyses (30 in the 250 mg once daily group, 30 in the 250 mg twice daily group, 29 in the 500 mg once daily group, and 31 in the placebo group). The mean relative change from baseline in liver fat content at week 12 was −1·1% in the placebo group, −1·0% in the 250 mg once daily group (mean difference versus placebo 0·1% [95% CI −15·4 to 15·7], p=0·99), −14·3% in the 250 mg twice daily group (−13·1% [–28·1 to 1·8], p=0·084), and −14·7% in the 500 mg once daily group (−13·5% [–28·5 to 1·4], p=0·076). At least one treatment-emergent adverse event occurred in 23 (77%) of 30 patients in the 250 mg once daily group, 20 (67%) of 30 patients in the 250 mg twice daily group, 21 (72%) of 29 patients in the 500 mg once daily group, and 21 (68%) of 31 patients in the placebo group. The most common treatment-emergent adverse event was diarrhoea (five [17%] of patients in the 250 mg once daily group, seven [23%] in the 250 mg twice daily group, six [21%] in the 500 mg once daily group, and none in the placebo group). No life-threatening events or treatment-related deaths occurred. Interpretation: PXL770 treatment did not meet the primary outcome of liver fat improvement compared with placebo. Treatment was well tolerated. Given indications that metabolic features improved with PXL770 treatment, AMPK activation might be a promising pharmacological target for patients with type 2 diabetes and NAFLD, and could also be considered for further assessment in patients with non-alcoholic steatohepatitis. Funding: Poxel.